Targeting STING signaling for the optimal cancer immunotherapy - Xu, Yan; Xiong, Ying (Frontiers in Immunology, 2024)
Despite the transformative impact of anti-PD-1/PD-L1 therapies, challenges such as low response rates persist. The stimulator of interferon genes (STING) pathway, a crucial element of innate immunity, emerges as a strategic target to overcome these limitations. Understanding its multifaceted functions in cancer, including antigen presentation and response to DNA damage, provides valuable insights. STING agonists, categorized into cyclic dinucleotides (CDNs) and non-CDNs, exhibit promising safety and efficacy profiles. Innovative delivery systems, including antibody-drug conjugates, nanocarriers, and exosome-based therapies, address challenges associated with systemic administration and enhance targeted tumor delivery. Personalized vaccines, such as DT-Exo-STING, showcase the adaptability of STING agonists for individualized treatment. These advancements not only offer new prospects for combination therapies but also pave the way for overcoming resistance mechanisms. This review focuses on the potential of targeting STING pathway to enhance cancer immunotherapy. The integration of STING agonists into cancer immunotherapy holds promise for more effective, personalized, and successful approaches against malignancies, presenting a beacon of hope for the future of cancer treatment.